Influence of Chloride Ion on the Toxicity of Heavy Metal Mercury upon Vibrio parahaemolyticus - Balasubramanian, R. Premalatha*, A. Purushothaman, T. (Recent Research in Science and Technology, 2011)
Heavy metal pollutants released into the coastal region certainly influence the bacterial population leading to the formation of metal resistant forms. The toxicity of mercury to different species of bacteria also vary. Among bacteria Vibrio parahaemolyticus play an important role in the disease of marine animals and human beings as pathogens. Hence the present study was aimed to understand the effect of mercury on the survival of two V. parahaemolyticus strains isolated from polluted uppanar estuary at different concentrations. (0, 1, 10, 25, 50 and 100 ppm) in the absence and presence of Nacl (1.75 and 3.5%) was carried out. Toxicity of mercury showed that Ã‚Â V. parahaemolyticus gradually decreased upto 1 ppm mercury and then there was a decline at higher concentration of mercury.